A nucleic acid-directed, red light-induced chemical reaction - Fülöp, Annabelle; Peng, Xiaohua; Greenberg, Marc M.; Mokhir, Andriy (Chemical communications, 2010)
The first nucleic acid-directed catalytic photochemical reaction that is induced by nontoxic red light was developed. This reaction is fast, high yielding, sequence specific, and enables one to functionalize an oligonucleotide.